P358 Factors associated with disability in inflammatory bowel disease (IBD): A cross-sectional study in outpatients. (16th January 2018) - Costa, J M; Matos, D; Costa, R; Arroja, B; Gonçalves, R; Soares, J B
Abstract: Background: The Inflammatory Bowel Disease-Disability Index has recently been validated to measure IBD-disability. The objectives of study were to assess the IBD disability in outpatient settings and to evaluate what sociodemographic, clinical and psychological factors are associated with greater disability. Methods: Between August and October of 2016, patients with an established diagnosis of Crohn's disease (CD) or ulcerative colitis (UC) for at least 3 months and followed up at outpatient clinic were invited to participate. Socio-demographic and clinical data were collected through the clinical process and interview. Optimism and disability were evaluated by applying, personally or by phone, the validated Portuguese versions of the Revised Life Orientation Test (LOT-R) and IBD-DI respectively. The association between sociodemographic, clinical and psychological variables (optimism) and IBD-DI (scale 0–100, proportional to the reported disability) was determined by univariate and multivariate analysis. Results: A total of 143 patients (51% CU) were analysed, 85.3% in clinical remission, with a median IBD-DI-PT score of 17.9 ± 10.7, with no significant differences between DC and CU ( p = 0.944). In univariate analysis, sex ( p = 0.001), high schooling ( p = 0.018), the perception of the number of faults ( p = 0.02), the rheumatologic manifestations ( p = 0.005), the number of comorbidities ( p = 0.002), the psychotropic drugs ( p = 0.043), and the LOT-R ( p < 0.001) showed statistically significant associations. In multivariate analysis sex ( p = 0.001), the number of comorbidities ( p = 0.027) and the LOT-R (p <0.001) are significant. Conclusions: Outpatients with IBD reported low levels of IBD-disability, which can be explained by the high percentage of patients in clinical remission. Comorbidities and psychological factors (optimism) emerged as the main predictive factors of greater disability, reinforcing the importance of multidisciplinary approach of these patients.